Microstructure and Impact Toughness of X70–L245 Butt Girth Weld in Natural Gas Station. (September 2020) - Ren, Junjie; Ma, Weifeng; Hui, Wenying; Tong, Ke; Nie, Hailiang; Wang, Ke; Dang, Wei; Cao, Jun
Abstract: At present, the numerical simulation and safety evaluation of girth welds are based on the properties of tubular materials, which cannot truly reflect the properties of girth welds. Based on the investigation results of girth weld in the station, this paper took X70 (21mm) and L245 (12mm) joints with large material and wall thickness gap in the station as research objects, prepared girth weld according to the welding process in the project site, and studied the structure and impact toughness of the joints. The microstructure of weld zone was analyzed by optical microscope. Charpy impact toughness increased from the center of weld to both sides, and the center of weld was the lowest. On X70 side, the impact toughness of FGHAZ is the highest and the impact energy is about 200 J, which is significantly higher than the weld center. The impact toughness near the fusion line on side L245 is the highest, but significantly smaller than that on side X70. Grain refinement, interlacing structure and M/A structure are conducive to the improvement of impact toughness. In this kind of girth weld, the center of the welding seam is the weakest area, and the X70 side has a significantly higher toughness.